Post-crisis Situation of German Economy under Analysis - Roxana Gabriela HODOROGEL; Robert CHIRA (Revista de Management Comparat International)
In 2010, both the EU and euro zone registered economic growth, mainly due to Germany's performance. Seen as a whole, the German economy grew stronger last year than in the last two decades, so that, for most sectors, 2010 brought gains despite experts’ negative forecasts. This positive development was, however, due to measures taken by the government in Berlin since the end of 2008, after the global financial crisis started. For 2011 the German authorities still expect a GDP growth in real terms of 2.3% and economic experts speak even of 2.8%, which would be an evolution over the euro zone states average economies.